MYTHONYMS AS MARKERS OF NATIONAL AND CULTURAL TRADITION IN THE TEXT OF THE ANCIENT GREEK NOVEL BY ACHILLES TATIUS - ЧАКАЛ, Інеса (Київський національний університет імені Тараса Шевченка, 2023)
The article attempts to generally characterize the proper mythological vocabulary as an integral component of the onomastic background of the novel “Leucippe and Clitophon” written by the ancient Greek writer of the 2nd century A.D. Achilles Tatius. The purpose of the research was a typological, lexical-semantic and functional-stylistic analysis of mythonyms detected in the text of the novel. The mythospace of the ancient Greek novel determined the specifics of the verbal functioning of mythological objects, which were analyzed with the involvement of descriptive and quantitative analysis methods. In the structure of the onymic space of the novel “Leucippe and Clitophon” among anthroponyms, toponyms, ethnonyms / katoikonyms and chrononyms, the mythonyms occupy a key place (out of 181 onyms, 77 lexemes are mythonyms). Although most of them belong to the onomastic periphery in the novel’s text (a total usage is 295 words), they still have a defining role in the idiostyle of Achilles Tatius. The scientific novelty of the obtained results lies in the firstever systematic analysis of mythonyms in the novel “Leucippe and Clitophon”, involving a classification of mythological nominations by lexical meaning into three groups: 1) names of ancient gods, deities and mythical creatures, 2) names of heroes and heroines of myths or ancient works, and 3) names of historical figures (writers, statesmen, inventors, kings, commanders); their functional and stylistic features. Mythonyms appear in the novel in descriptions of artistic paintings, mythical stories, and comparisons with novel characters. The novel’s heroes make sacrifices to the gods and turn to them in oaths, supplications and prayers. The names of gods and goddesses ἡ Ἀφροδίτη, ἡ Ἄρτεμις, ὁ Ἔρως and ὁ Ζεύς are dominant among mythonyms in the text of the novel, and we consider them as keywords. Conclusions. Mythological proper vocabulary performs characteristic and artistic-aesthetic functions in the novel’s text as an important means of cohesion.

У статті зроблено спробу охарактеризувати в загальних рисах пропріальну міфологічну лексику як невід’ємний складник ономастичного фону роману «Левкіппа і Клітофонт» давньогрецького письменника ІІ ст. н. е. Ахілла Татія. Метою дослідження був типологічний, лексико-семантичний і функційно-стилістичний аналіз міфонімів, уживаних у тексті роману. Міфопростір давньогрецького роману визначив специфіку вербального функціонування міфологічних об’єктів, які були проаналізовані із залученням описового і методу кількісного аналізу. У структурі онімного простору роману «Левкіппа і Клітофонт» серед антропонімів, топонімів, етнонімів / катойконімів і хрононімів міфоніми займають ключове місце (із 181 оніма 77 лексем – міфоніми). Незважаючи на те що більшість з них належать до ономастичної периферії в тексті роману (усього 295 слововживань), все ж таки мають визначальну роль для ідіостилю Ахілла Татія. Наукова новизна одержаних результатів полягає в тому, що в роботі вперше здійснено системний аналіз міфонімів у творі «Левкіппа і Клітофонт»; міфологічні номінації класифіковано за лексичним значенням на три групи: 1) імена античних богів, божеств і міфічних істот, 2) імена героїв і героїнь міфів або античних творів, 3) імена історичних постатей (письменників, державних діячів, винахідників, царів, полководців); з’ясовано їхні функціонально-стилістичні особливості. Міфоніми фігурують у романі в описах художніх картин, у міфічних оповідях, у порівняннях із персонажами роману. Герої роману здійснюють богам жертвоприношення, звертаються до них у клятвах, благаннях і молитвах. Домінантними серед міфонімів у тексті роману виявилися імена богів і богинь ἡ Ἀφροδίτη, ἡ Ἄρτεμις, ὁ Ἔρως та ὁ Ζεύς, які вважаємо ключовими словами. Висновки. Міфологічна пропріальна лексика виконує в тексті роману характеризувальну та художньо-естетичну функції, виступає важливим засобом когезії тексту.
МІФОНІМИ ЯК МАРКЕРИ НАЦІОНАЛЬНО-КУЛЬТУРНОЇ ТРАДИЦІЇ В ТЕКСТІ ДАВНЬОГРЕЦЬКОГО РОМАНУ АХІЛЛА ТАТІЯ
Keywords: міфоніми; міфопростір; лексико-семантичний аналіз; функційно-стилістичний аналіз; ідіолект; давньогрецький роман; Ахілл Татій; mythonyms; mythical space; lexical-semantic analysis; functional-stylistic analysis; idiolect; ancient Greek novel; Achilles Tatius